2011
DOI: 10.1080/02705060.2011.633341
|View full text |Cite
|
Sign up to set email alerts
|

Condition, length–weight and length–length relationships of the silver hatchet Chela,Chela cachius(Hamilton, 1822) in the Old Brahmaputra River of Bangladesh

Abstract: The silver hatchet chela, Chela cachius (Hamilton, 1822), is a cyprinid freshwater species, commercially important for both subsistence and artisanal fisheries in Bangladesh. This study describes the length-weight relationship (LWR), length-length relationship (LLR) and the condition of this minnow species from the Old Brahmaputra River in Bangladesh. In this study, 12 monthly samples totalling 2400 specimens (1172 male; 1228 female) collected from November 2004 to October 2005 were used to conduct this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
2
0
1
Order By: Relevance
“…).The b values for Salmostoma bacaila, Botia lohachata, Ompok pabda and Trichogaster lalius were found to be quite close to the findings ofBorah et al (2017);Gupta, Sarkar, Bhardwaj, and Pal (2011);Hossain et al (2012)andIslam and Mia (2016) respectively Ahmed, Hossain, and Ohtomi (2012). found that b value in C. cachius ranged from 2.42 in October to 3.55 in July from old Brahmaputra River, Bangladesh.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…).The b values for Salmostoma bacaila, Botia lohachata, Ompok pabda and Trichogaster lalius were found to be quite close to the findings ofBorah et al (2017);Gupta, Sarkar, Bhardwaj, and Pal (2011);Hossain et al (2012)andIslam and Mia (2016) respectively Ahmed, Hossain, and Ohtomi (2012). found that b value in C. cachius ranged from 2.42 in October to 3.55 in July from old Brahmaputra River, Bangladesh.…”
supporting
confidence: 70%
“…Ahmed, Hossain, and Ohtomi (2012) found that b value in C. cachius ranged from 2.42 in October to 3.55 in July from old Brahmaputra River, Bangladesh. The b value for S. cascasia in this study fit the expected range (2.81-3.15)…”
Section: The B Values For Salmostoma Bacaila Botia Lohachata Ompok mentioning
confidence: 99%
“…Perairan Pulolampes Brebes merupakan perairan dangkal dengan gugusan karang jeruk yang baik bagi habitat ikan teri dan menjadi daerah penangkapan ikan nelayan. Hal ini diperkuat oleh pendapat Hutomo et al (1987) 1] yang menyatakan bahwa Teri mempunyai sifat pelagik yang umumnya hidup dalam gerombolan (shoaling), menghuni perairan pesisir dan estuaria, tersedianya banyak makanan dan kadar garam yang relatif rendah.…”
Section: Pendahuluanunclassified
“…Condition was compared among sections using mass ( M ) as the dependent variable and L S as the covariate. This relationship has been established as a good predictor of fish condition and was compared between sections using an ANCOVA (Le Cren, ; Petrakis & Stergiou, ; Moutopoulis & Stergiou, ; Ahmed et al , ). To determine if fishes were compensating for a reduction in nutrients by increasing consumption, an ANCOVA model was used for each species during each sample with L S as the covariate, total mass of prey items in the GIT as the dependent variable and section of stream as the independent variable.…”
Section: Methodsmentioning
confidence: 99%